Suksesi Di Afganistan Menurut Hukum Internasional - Farhan Juneth Paisuly; Popi Tuhulele; Welly Angela Riry (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Succession is a change or replacement of a legal subject by another legal subject. Similar to Garner's opinion, this is also stated in civil law that succession means the replacement of one legal subject by another legal subject. For example, because the first legal subject died. Although not very precise, the definition of succession is used in international law and is applied to two events of state change, namely state succession and government succession. This legal research uses normative juridical law or library law research, namely legas researchconducted by examining literature or secondary data consisting of primary legal materials, secondary law, and tertiary law. These materials are then methodicaly collected, reviewed, and conculusions draw with repect to the problem being investigated. In particular the legal implications of state succession under international law. The results of the study show that these arrangements are reflected in three conventions governing state succession according to international law, namely: First, the 1969 Vienna Convention on the Law of Treaties, which adheres to the principle of rebus sic stantibus, which states that if there is a fundamental change, circumstances can be used to terminate or withdraw from the agreement; Second, the 1978 Vienna Convention on Succession of States in Relation to International Agreements, which only applies to written international agreements attached to an agreement; and Third, the 1982 Vienna Convention on the Successional Status of States has legal consequences for state archives, private property rights, public property rights, and state property rights.